Seeds to support future growth : (re)establishment of the dormant Protea Village - Le Roux, Gys (School of Architecture, Planning and Geomatics, 2016)
This thesis addresses and critiques housing delivery processes currently realised by South African national government. It is argued that a major flaw in this process is resultant from the role taken by government as provider rather than facilitator. Government takes pride in the x-amount of new housing units being built but in effect is rolling out suburbs which stifles quality living. The resultant environments that are created very few people can call home and be proud to do so. Government housing in many cases results in housing that _ does not respond to user requirement and need, _does not reflect shifting family structures and creates environments which is mono-functional. In many 'completed' housing projects the result is that as soon as residents move into newly built homes a process of alteration and extension is undertaken as to respond to individual needs or provide some form of economic support. Within this thesis I would like to challenge these issues and propose a solution whereby we allow for some sense of uncertainty and change; a solution whereby the user plays an active role in the process of creating their homes. This premise is investigated through an approach of incremental development initiated by a core/starter unit. The process of expansion and alteration is then also explored with the promise of providing economic opportunities within communities.